Pengaruh Metode Pembelajaran dan Kreativitas Terhadap Hasil Belajar Siswa di SMA 7 PSKD Depok - Victor Andreas Jusup (Jurnal Pendidikan Sejarah, 2014)
Abstract The purpose of this study was to determine the impact of the task of learning methods, and its relation to the creativity of the students to the history learning outcomes at SMA 7 PSKD Depok. The research method used was experimental. test instruments are also used to measure the learning outcomes of history, and questionnaires used to measure the creativity of students in learning history. A total of 32 participants will be randomly selected. Data analysis will be performed by using two way variance analysis. The findings of the study will be demonstrate: 1) a higher student’s history learning outcome of those who were taught by Recitation instructional methodology compared to those who were taught by conventional method. 2) There is an interaction effect between instructional methodology and student’s creativity level on history learning outcome. 3) History learning outcome of students who has higher creativity level and were taught by Recitation method are higher than those with the same level of creativity but were taught by conventional method. 4) History learning outcome of students who has lower creativity level and were taught by Recitation methodology are not below those with the same creativity level but were taught by conventional method. Keywords : history learning outcome, history instructional methodology, student’s creativity level.